Moderasi Beragama Pada Masa Pandemi Covid 19 - muna waroh (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2022)
This article aims to study the importance of religious moderation to learn and convey to the Indonesian people. Considering that the majority of Indonesian people are Muslims, besides that, the Muslim community also coexists with non-Muslims. Surely this is very necessary regarding the science of religious moderation, in order to provide understanding to the public. The method used is a qualitative approach with a descriptive method. The results of this study will show the efforts of the government in increasing the moderation of religious communities in Indonesia by finding a solution in preventing conflicts and divisions in society during the current pandemic, so that it is hoped that the Indonesian people can tolerate each other between religious communities.Keywords: Religious Moderation, Covid 19 Keywords: Religious Moderation, Covid 19